2019
DOI: 10.1002/jbmr.3905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic or Resistance Exercise, or Both, on Bone Mineral Density and Bone Metabolism in Obese Older Adults While Dieting: A Randomized Controlled Trial

Abstract: Weight loss therapy of older adults with obesity is limited by weight loss–induced decrease in bone mineral density (BMD), which could exacerbate ongoing age‐related bone loss and increase the risk for fractures. Therefore, it is recommended that weight loss therapy of older adults with obesity should include an intervention such as regular exercise to reduce the concomitant bone loss. However, the most appropriate exercise types to combine with weight loss therapy in this older population is unknown. In a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 46 publications
4
41
0
2
Order By: Relevance
“…Out of the 24 studies identified, five had already been included in the WHO report [42,47,66,68,71]. Therefore, the expanded search found 19 additional studies [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95].…”
Section: Expanded Search For Individual Studiesmentioning
confidence: 99%
“…Out of the 24 studies identified, five had already been included in the WHO report [42,47,66,68,71]. Therefore, the expanded search found 19 additional studies [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95].…”
Section: Expanded Search For Individual Studiesmentioning
confidence: 99%
“…The length of time the study was conducted may not have been beneficial to demonstrate enough change in bone mineral density. This is worth further exploration considering a study recently published on older obese adults that showed combining aerobic and resistance exercise protected against loss of BMD that can occur during weight loss efforts (Armamento-Villareal et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It depends on the availability of insulin and requires a cautious control of glycemia [ 66 ]. It is necessary to monitor insulin administration to keep up with the CHO consumption [ 14 ], considering the possible effects of exercise reduction of the athletes before the competition. Hence, glycemic supervision is essential for GL.…”
Section: Training and Competitionmentioning
confidence: 99%
“…Furthermore, diabetic subjects may undergo several changes in the connective tissue, including bone, tendons and cartilage [ 6 ]. Therefore, some musculoskeletal disorders are more common in diabetic subjects and include osteoarthritis [ 7 ], tendinopathy [ 8 ], fractures [ 9 ], intervertebral disc degeneration [ 10 , 11 ] and decreased bone mineral density (BMD) [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%